Analisis Korelasi Nilai Tukar Rupiah terhadap Dolar Amerika Serikat dan Pertumbuhan Ekonomi Indonesia dalam Perspektif Islam - Ahmad Nauval Tamam; Muslikhati Muslikhati (Department of Islamic Economic Law, Institut Agama Islam (IAI) Al-Qolam, 2019)
This research aims to analyze the exchange rate of the Rupiah and United States Dollar with Indonesia's economic growth period in 2004 until the year 2016 in Islamic Perspective. The results of this study indicate that the Islamic Perspective Views of causality Between the exchange rate of the Rupiah And United States Dollar With Indonesia's economic growth period in 2004 until the year 2016 are specified in two important things: 1) There is no causality relationship, but there is a one-way relationship between variable exchange rates of Rupiah and United States Dollar with Indonesia’s economic growth variables from the year 2004-2016. Rupiah exchange rate variable significant and influential correlated against Indonesia's economic growth with the value of the significance of the test based on Granger Causality Test 0.0334, 2) Exchange rates in Islamic can be said to adhere to the system “Managed Floating”, and economic growth in Islamic the purpose develop resources at once empowering nature in enhance human dignity.